The Structure, Property, Preparation and Application of Carbon Nanotube in Biosensors - Wang, Jingdong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Instruments known as biosensors are highly sensitive to biological materials and have the ability to detect concentrations by converting them into electrical signals. High-sensitivity detection of complex biological samples can be achieved by utilizing the specificity and sensitivity of biomolecules. Due to the high sensitivity, high selectivity and important applications of biosensors, they have attracted much attention. It is reported that the materials used in biosensors have a significant impact on their detection sensitivity. Therefore, exploring new functional materials to modify biosensors is helpful to improve the sensitivity and the accuracy of the biosensors. Carbon nanotubes, exhibit good stability of structure and excellent performance, such as mechanical properties, thermal conductivity and optical properties. As a result, in recent years, research on using carbon nanotubes for biosensor modification has gained a lot of attention. The characteristics and categorization of carbon nanotubes are described in this article. The process required for prepare carbon nanotubes and different biosensors based on carbon nanotubes are also outlined. Additionally, the methods for creating carbon nanotubes and how they are used in biosensors are discussed.